Drug Checking: A prevention measure for a heterogeneous group with high consumption frequency and polydrug use - evaluation of zurich's drug checking services - Schaub Michael; Buecheli Alexander; Hungerbuehler Ines (BMC, 2011)
Abstract Background The increasing party culture in Zurich presents new challenges, especially regarding the consumption of alcohol and so-called party drugs. Streetwork, the youth advisory service of the city of Zurich, has provided onsite and stationary Drug Checking facilities since 2001 and 2006, respectively. Drug Checking always involves filling out an anonymous questionnaire, which allows the collection of important information about a largely unknown group of users and their consumption patterns. Methods The questionnaires assessed sociodemographic characteristics, consumption patterns, Drug Checking experiences, information behavior and social support. The collected data were statistically analyzed by the Research Institute for Public Health and Addiction (RIPHA). Results The majority of Drug Checking service patrons were male and between 20 and 35 years old. These patrons reported high lifetime prevalences and high consumption frequencies of legal and illegal substances, and they often reported polydrug use. Aside from tobacco and alcohol, the most consumed drugs during typical party nights were ecstasy, amphetamines, cannabis and cocaine. Party drug consumers using Drug Checking services form a heterogeneous group with respect to sociodemographic characteristics and consumption patterns. Users of the onsite Drug Checking facilities were significantly younger, were less experienced with drug testing, and reported more polydrug use than users of the stationary Drug Checking service. Conclusions Drug Checking combined with a consultation appears to be an important harm reduction and prevention measure that reaches a group of consumers with high consumption frequency and polydrug use. Because of the heterogeneity of the target group, different prevention measures must be offered and embedded in an overall local concept.